THE USE OF VISUALIZATION STRATEGY TO IMPROVE READING COMPREHENSION OF THE TWELFTH GRADE STUDENTS OF SMK WIRA HARAPAN IN ACADEMIC YEAR 2019/2020 - Wirastuti, I Gusti Agung Putri; Arsana, Anak Agung Putu; Dewi, Ni Putu Ayu Parsining (IKIP SARASWATI TABANAN, 2020)
The study aims to improve reading comprehension of the twelfth grade students of SMK Wira Harapan through visualization strategy. Visualization strategy in this present study has four elements, such as: Reading, Discussing, Sketching, and Sharing. Based on the mean score of the pre-test that was only 41.82, the subjects’ reading comprehension was still low. To enhance the improvement of their ability, the researcher prepared some instruments to collect the data, namely: pre-test, post-test and questionnaire. The study was divided into two cycles which consisted of four sessions. The result of the mean score in cycle I was 71.64. The minimum passing grade of the twelfth grade students of SMK Wira Harapan was 80, it caused the researcher continued the research by conducting post-test in cycle II and the result of the mean score was 82.30. The finding showed that was constant improvement of the students after implementing visualization strategy. In addition, the result of the questionnaire showed that more than 90% agreed with this technique. In conclusion, the study showed that reading comprehension skill of the twelfth grade students of SMK Wira Harapan in academic year 2019/2020 could be improved through visualization strategy